(untitled) (International Journal of Communication Systems and Network Technologies, 2019)
Now a day’s mobile ad-hoc network is gaining popularity due to system application demands such as internet of things (IoT) based sensor deployment, home surveillance system, atmospheric emergency data gathering, Ad-hoc hotspot communication establishment etc. The new generation of communication focuses to handle the entire electronic devices through sensor with lightweight processes model (LWP) for real time data acquisition and monitoring. In this paper we analyze research gap in existing schemes with issues and challenges towards the efficient path selection with trusted communication which provides the strength to the new age of communication technology. This paper explores various aspects of capability based trusted routing scheme in Mobile Ad Hoc Network for improvising the network performance.